Catharine McClellan (1921- ) - Cruikshank, Julie (ARCTIC, 1984)
. Catharine McClellan's position in North American anthropology is important, but equally important is her recognition in the Yukon. For her academic work she has received distinction; in the Yukon, she has become part of the folklore. Not infrequently, anthropologist refer to informants" as "my people" and speak of "trips to the field". A generation of Yukon Indians ranging from elderly people to adults who were toddlers when she first arrived refer to Catharine McClellan as "our Kitty" and see her primary residence as the Yukon with periodic "field trips" back to her university. They welcome her visits as those of a returning family member and regret her departures as temporary absences. Catharine McClellan is currently writing a book on Yukon Native History for the Council for Yukon Indians. She plans to write up more of her accumulated years of field research and to spend time, as she has for almost four decades, visiting her friends in the Yukon.